Differential effects of the loss of intrachain- versus interchain-disulfide bonds in the cystine-knot domain of von Willebrand factor on the clinical phenotype of von Willebrand disease - Tjernberg, Pernilla; Vos, Hans L.; Spaargaren-van Riel, Caroline C.; Luken, Brenda M.; Voorberg, Jan; Bertina, Rogier M.; Eikenboom, Jeroen C. J. (Thrombosis and Haemostasis, 2006)
Von Willebrand factor (VWF) contains a large number of cysteine residues, which all form disulfide bonds. Mutations of cysteines located in the cystine-knot (CK) domain of VWF have been identified in both qualitative type 2A (IID) and quantitative type 3 vonWillebrand disease (VWD).Our objective was to test the hypothesis that the difference in phenotype is related to whether the mutated cysteine residue is involved in either interchain- or intrachain-disulfide-bond formation. The effects of three cysteine mutations which are all located in the CK-domain of VWF, C2773S (type 2A(IID)), C2739Y (type 3), and C2754W (type 3), were studied by transient expression in 293T cells. Cotransfection of wild-type (wt) and C2773S VWF constructs reproduced the plasma phenotype of heterozygous type 2A(IID) patients, with normal to high levels of VWF antigen (VWF:Ag), absence of high-molecular-weight multimers, and the presence of intervening bands between the normal multimers.In contrast, single transfections of C2739Y or C2754W resulted in a quantitativeVWF defect with lowVWF:Ag levels, and co-transfections of wt and mutant constructs resulted in a 50% reduction of VWF:Ag and only a minor effect on VWF multimerization. We demonstrated N-terminal dimerization of VWF-C2773S and both Nand C-terminal dimerization of VWF-C2754W. Our data suggest that loss of a single disulfide bond in the CK-domain ofVWF leads toa recessive, quantitativeVWF deficiency if an intrachain-disulfide bond is involved, and to a dominant-negative, qualitative defect of VWF if an interchain-disulfide bond is involved.
Keywords: ADAMTS13; cysteine; dimerization; disulfide bond; multimerization